2020
DOI: 10.31234/osf.io/63dhn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Training Child Learners On Non-Native Vowel Contrasts with Phonetic Training: The Role of Task and Variability

Abstract: Acquiring a non-native speech contrast is often difficult. High variability phonetic training (HVPT) is a well-established method used to train learners on non-native phoneme contrasts: it critically uses high variability (HV) input after earlier studies using low variability (LV) input had proved unsuccessful. HVPT has since been successfully applied in many different studies with adult participants, but much less so with children. The current study further investigates the effect of input variability on phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…Floor effects would have likely been less of a concern given our learners are adults with some English experience. Furthermore, a similar kind of phonetic training paradigm but with 7-and 11-year-olds who had very little English experience showed improvement over a set of 8 training sessions, even if pre-tests scores were at chance (Brekelmans et al, 2020). Given that 1) our learners generally had more experience of English and 2) there is no reason to suspect that phonetic training per se only works for certain pre-test accuracy, we did not include a lower cutoff for pre-test scores.…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Floor effects would have likely been less of a concern given our learners are adults with some English experience. Furthermore, a similar kind of phonetic training paradigm but with 7-and 11-year-olds who had very little English experience showed improvement over a set of 8 training sessions, even if pre-tests scores were at chance (Brekelmans et al, 2020). Given that 1) our learners generally had more experience of English and 2) there is no reason to suspect that phonetic training per se only works for certain pre-test accuracy, we did not include a lower cutoff for pre-test scores.…”
Section: Participantsmentioning
confidence: 99%
“…Finally, Brekelmans et al (2020) also investigate the role of high versus low talker variability in 7-year-olds and 11-year-old Dutch children learning English vowels. They found that both age groups improved as a result of eight training sessions, but 7-year-olds did not show any generalisation abilities regardless of which input variability condition they were in.…”
Section: Child Learnersmentioning
confidence: 99%
See 3 more Smart Citations